The Impact of Corporate Social Responsibility, Market Equity Value, Information Asymmetry, Market Beta, and Earnings Management on Equity Capital Costs in Property and Real Estate Companies Listed on the Indonesian Stock Exchange in 2019-2021 - Rosita Pasaribu; Bayu Wulandari; Nikmat Kasih Telaumbanua; Magdalena Silalahi; Tionar Regina Simarmata; Mhd Zulkifli Hasibuan (Kusuma Negara Business School, 2023)
This study aims to analyze the Influence of Corporate Social Responsibility, Equity Market Value, Information Asymmetry, Market Beta, and Earnings Management on the Cost of Equity Capital in Property and Real Estate Companies listed on the Indonesia Stock Exchange from 2019 to 2021. The type of data used in this study is secondary data sourced from the financial reports of Property and Real Estate Companies from 2019-2021. The sample selection method used in this study is purposive sampling and the data processing method used is the multiple linear regression method, T-Test and F-Test through SPSS 25 software. The results of this study show that Corporate Social Responsibility, Equity Market Value, Information Asymmetry, Market Beta, and Earnings Management simultaneously have a significant effect on the Cost of Equity Capital. Partially, the Equity Market Value has a negative effect on the Cost of Equity Capital. Meanwhile, Corporate Social Responsibility, Information Asymmetry, Market Beta, and Earnings Management partially do not have an effect on the Cost of Equity Capital.